2018
DOI: 10.13057/biodiv/d190211
|View full text |Cite
|
Sign up to set email alerts
|

Traditional markets and diversity of edible plant trading: Case study in Ujung Berung, Bandung, West Java, Indonesia

Abstract: Iskandar BS, Iskandar J, Irawan B, Partasasmita R. 2018. Traditional markets and diversity of edible plant trading: Case study in Ujung Berung, Bandung, West Java, Indonesia. Biodiversitas 19: 437-452. Traditional markets are where traders and buyers meet; places where the supply and demand activities of selling and buying between traders and buyers occur. Buying and selling activities are realized based on the practice of bargaining, made possible by a negotiated willingness to slide a price. In bargaining, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 8 publications
1
48
1
9
Order By: Relevance
“…The urban bird market can be categorized as one of the Indonesian traditional markets. The traditional market may be defined as the traders and buyers meet, places where the supply and demand activities of buying and selling commodities, including birds between traders and buyers, occurs (Iskandar et al 2018).…”
Section: Study Sitementioning
confidence: 99%
“…The urban bird market can be categorized as one of the Indonesian traditional markets. The traditional market may be defined as the traders and buyers meet, places where the supply and demand activities of buying and selling commodities, including birds between traders and buyers, occurs (Iskandar et al 2018).…”
Section: Study Sitementioning
confidence: 99%
“…Lebih dinyatakannya bahwa pemilik nurseri menggunakan managemen dalam pembi bitan, pemeliharaan, dan pemilihan tanaman untuk mendukung pengembang an dan kelangsungan nurseri. Tanaman diperjual-belikan di nurseri (Sihotang et al 2019) dan pasar (Iskandar et al 2018) bervariasi antar satu pedagang dengan pedagang lainnya.…”
Section: Abstrakunclassified
“…Pasar tradisional, pasar modern (Iskandar et al 2018) dan nurseri (Sihotang et al 2019) menjadi sumber utama dalam penyediaan tanaman di daerah perkotaan yang digunakan sebagai peneduh, penghasil buah, maupun sebagai tanaman pekarangan. Setiap lokasi perdagangan tanaman memiliki kelebihan dan kekurangan.…”
Section: Abstrakunclassified
See 1 more Smart Citation
“…As a result, ecological aspects of agroecosystems and socio-cultural aspects of rural people in both villages, Sukapuran and Tarumajaya have dramatic changes. Based on study on ethnobotany revealed that modernization of agricultural system and consumption changes of rural people have caused changes of traditional diversity of plants (Brush 2000;Iskandar, Iskandar and Partasasmita 2018). Both villages Sukapura and Tarumajaya were predominantly resided by Sundanese people.…”
Section: Study Areamentioning
confidence: 99%